Representing Personal and Professional Identities in Policing: Sources of Strength and Conflict. (Public Administration Review, 2022)
Representing diverse identities in government is important for equal employment, symbolic benefits, and opportunities to improve public service outcomes. This article uses qualitative interviews with 32 frontline police officers to examine the ways in which personal and professional identities intersect to promote or impede those benefits. The findings highlight how holding similar sociodemographic identities with the public can be a source of strength as it pertains to promoting shared understanding and reducing the social distance that comes with identity incongruence. However, internal identity conflicts arise as White officers overcome culture shock and endure learning curves, whereas officers of color navigate the dual pressures of empathetic treatment (that comes with shared personal identity) versus arms‐length treatment (that comes with professional identification). Even then, as seen in this study, the way officers treat and interact with the community is imperative and can overcome symbolic identity barriers.